Effect of aqueous and hydrometallic leaf extracts of Smallanthus sonchifolius (Popp.) H. Rob. in renal, hepatic and pancreatic metabolism of type 2 diabetic rats - Moreira , Bruna Souza; Jantara, Adrielly; Oliveira , Tiago; Souza , Carolina Ribeiro Noronha de; Oliveira , Rafael Pires; Reis , Débora Raquel Mergen Lima (Seven Editora, 2023)
Diabetes mellitus affects 415 million people worldwide, 81 to 91% of whom are type 2. The concern with the treatment of this disease leads to a growing search for complementary therapies, such as the use of medicinal plants. Smallanthus sonchifolius (Popp.) H. Rob.,  belonging to the Asteraceae family, is a tuber native to the Andes Mountains popularly known as Yacon, which has therapeutic properties. The objective of this research was to evaluate the effect of the use of Yacon's aqueous and hydrometallic extracts on the metabolism of normal and diabetic animals. Male Wistar rats (14 weeks) were divided into control and diabetic groups. The diabetes was caused by intraperitoneal injection of streptozotocin. Once the diabetic status was confirmed, the treatment was started with an infusion of 5.5g/kg/day of dry leaves and an extract of 7.5mL/kg/day, distributed in bottles according to the weight of the animal, and animals that received only water were controlled. Fifteen days after the beginning of therapy, the rats were anesthetized and blood samples were collected for analysis. After euthanasia, the tissues were removed for analysis of cytotoxic effect. The alkaline phosphatase enzyme in the diabetic groups was elevated, indicating a possible injury to the bile ducts. The urea and albumin tests also showed variation, suggesting renal injury due to diabetes, which was confirmed by histological analyses. The normal group treated with aqueous extract also presented renal injury, proving the toxicity of the extract. DOI:https://doi.org/10.56238/sevened2023.006-047